ADSORPTION STUDIES OF SOME DYES AND METAL COMPLEXES ON GARLIC HUSK- A CHEAP NATURAL ADSORBENT - K. S. GEETHA; S. L. BELAGALI (The Bioscan, 2012)
The present work deals with the adsorption study of some metals and dyes on cheap natural adsorbent- the garlic husk, which is treated with acid before adsorption process. Metals are made to react with ligand which gives colored solution and was used for adsorption studies. The reagents were kept in contact with adsorbent reacted in presence of acidic or alkaline or in neutral condition. pH condition will be different for different metals and dyes, depending on the rate of adsorption. Along with this, other parameters like effect of dose, concentration of adsorbate, contact time etc are studied and found that the adsorption increases with dose and contact time but decreases with concentration. The adsorption isotherm studies like Frendlich and Langmuir model were found to be favorable.